FINITE ELEMENT ANALYSIS OF CHIRAL HONEYCOMB WITH ELLIPTICALLY STRUCTURED CENTRAL NODE (International Journal of Engineering Sciences & Management Research, 2015)
This paper investigates the Design and Analysis of the innovative morphing Airfoil using the Auxetic Structure (Chiral Structure). This Structure is selected because it undergo larger displacement with limited Straining of its components and its unique deformation characteristics, which produce theoretical, in-plane Poisson’s ratio of -1. Different configuration of chiral structure is compared. Aluminum Alloy AL6061-T651 material is considered for all the structural elements. The objective of this paper is to investigate the compliance characteristics of the Airfoil with chiral structure as core. Finite Element Model is developed and the structural Analysis is performed. The advantage associated with the use of Auxetic Structure in the Airfoil is investigated by comparing the result from the previous investigations. The results are captured and plotted.